An introduction to the history of the principal states of Europe / begun by Baron Puffendorf ; continued by Mr. de La Martiniere ; improved by Joseph Sayer, Serjeant at law. - Pufendorf, Samuel, Freiherr von, 1632-1694. (Tufts University. Tisch Library., 2015)
A new edition revised and corrected.; 1 online resource (2 volumes, [1] leaf of plates) : folded illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog, T141115